2020
DOI: 10.3390/s20102757
|View full text |Cite
|
Sign up to set email alerts
|

Driving Factors and Future Prediction of Land Use and Cover Change Based on Satellite Remote Sensing Data by the LCM Model: A Case Study from Gansu Province, China

Abstract: Land use and cover change (LUCC) is an important issue affecting the global environment, climate change, and sustainable development. Detecting and predicting LUCC, a dynamic process, and its driving factors will help in formulating effective land use and planning policy suitable for local conditions, thus supporting local socioeconomic development and global environmental protection. In this study, taking Gansu Province as a case study example, we explored the LUCC pattern and its driving mechanism from 1980 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 65 publications
2
27
0
1
Order By: Relevance
“…In general, LULC change is the result of the comprehensive influences of so many complex and various factors [ 93 , 94 ]. Previous studies have revealed that on a global scale, human-driven land use/land cover change for most of the changes of land surface.…”
Section: Discussionmentioning
confidence: 99%
“…In general, LULC change is the result of the comprehensive influences of so many complex and various factors [ 93 , 94 ]. Previous studies have revealed that on a global scale, human-driven land use/land cover change for most of the changes of land surface.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are still some shortcomings in the Markov chain. The quantity demands under future scenarios are all set by humans according to their research needs [52,61]. For different RCP climate scenarios, the relationship between different forest tree species is not clear enough; thus, it is difficult to accurately establish the quantity requirements of different forest species.…”
Section: Discussionmentioning
confidence: 99%
“…The whole cycle process of landscape architecture planning and design includes the following main links: information acquisition -Environmental Analysis -design construction design evaluation design modification deepening design expression medium. AI reconfiguration design needs to be deeply involved in every link of planning and design, and establish a complete digital design strategy [19] . Digital information runs through the whole design cycle, and multiple software platforms exchange information and data with each other, so that the planning and design links can be smoothly connected, which makes the design from environmental cognition to final completion, and is always based on a relatively objective, fast, efficient and intuitive design system.…”
Section: Evaluation Algorithm Of Landscape Architecture Planning Pattern Reconstructionmentioning
confidence: 99%